Noncommutative Maxwell-Chern-Simons theory: One-loop dispersion relation analysis - Ghasemkhani, M.; Bufalo, R. [UNESP] (American Physical Society (APS), 2016)
In this paper, we study the three-dimensional noncommutative Maxwell-Chern-Simons theory. In the present analysis, a complete account for the gauge field two-point function renormalizability is presented and physical significant quantities are carefully established. The respective form factor expressions from the gauge field self-energy are computed at one-loop order. More importantly, an analysis of the gauge field dispersion relation, in search of possible noncommutative anomalies and infrared finiteness, is performed for three special cases, with particular interest in the highly noncommutative limit.